РОЛЬ ГЕКСОКИНАЗЫ И ГЛЮКОЗО-6-ФОСФАТДЕГИДРОГЕНАЗЫ В АДДПТАЦИЯХ ГИДРОБИОНТОВ-ОБРАСТАТЕЛЕЙ - (:unkn) unknown (Киев : Наукова думка, 1992)
На основании двухлетних наблюдений (1986—1987 гг.) дана характеристика изменений активности ключевых ферментов начального этапа гликолиза и пентозофосфатного пути (гексокиназы и глюкозо-6-фосфатдегидрогеназы) у массовых видов макрообрастания: гидроидов, ботриллюсов, мшанок. Динамика ферментативной активности изучена в периоды активного роста и угасания физиологической активности популяций, а также в условиях нормы и гипоксии. Обсуждается возможность использования параметра Г-6-ФДГ/ГК (соотношение активностей изучаемых ферментов) при биоиндикации.
Role of hexokinase and glucose-6-phosphatedehydrogenase in adaptations of hydrobiontic foulings
Mass hydromiontic foulings: hydroids, bothrilluses, pearlworts, have been analyzed for the dynamics of activity of the key enzymes at the first stage of glycolysis and pentophosphate path (hexokinase and glucose-6-phosphatedehydrogenase). Results are presented. A comparative analysis of the enzymes' activity was carried out at different developmental stages of the populations (active growth, ageing) as well as in norm and under hypoxia. It is supposed to use activity of the mentioned enzymes for description of the homeostasis in the studied species of hydrobionts under natural conditions of the habitat. It is supposed as possible to use the relation of activities of the enzymes T-6-FDGGK) in bioindication.